Actual causes of death in thyroid cancer patients in Korea: A Nationwide Case Control Cohort Study. Issue 1 (January 2020) - Kim, Kyeong Jin; Jang, Sujung; Kim, Kyoung Jin; An, Jee Hyun; Kim, Nam Hoon; Shin, Dong Yeob; Yoo, Hye Jin; Kim, Hee Young; Seo, Ji A; Kim, Nan Hee; Lee, Juneyoung; Choi, Kyung Mook; et al.
Abstract : Objective: Thyroid cancer (TC) incidence has increased robustly in Korea. However, the actual cause of death, overall mortality risk, and cause-specific mortality risk in TC patients have not been clearly elucidated. Design: Retrospective cohort study. Methods: We analyzed 4082 TC patients from the Korean National Health Insurance Service-National Health Screening Cohort (NHIS-HEALS, 2002–2013) with a median of 48-month follow-up. We compared these patients with 12 246 controls matched for age, sex, and histories of major cardiovascular disease (CVD) to investigate the cause of death and risks of overall and cause-specific mortality. Results: Overall, 61 deaths (1.5%) occurred in the TC group. The most common cause of death was TC-specific mortality (32.8%), followed by other malignancy-related mortality (31.1%) and CVD mortality (13.1%). The overall mortality risk was comparable between the TC and control groups (unadjusted hazard ratio (HR): 1.17; 95% confidence interval (CI): 0.87–1.58); the adjusted HR remained at 1.25 (95% CI: 0.90–1.74) after multivariate adjustment for body mass index (BMI), socioeconomic status (SES), smoking, alcohol consumption, and histories of hypertension, diabetes mellitus, and dyslipidemia. In addition, there was not enough evidence against the surmise that the CVD mortality risk was similar between the TC and control groups, with an HR of 0.50 (95% CI: 0.22–1.16) after adjustment for CVD risk factors. Conclusions: Excellent overall survival was observed in TC patients. The most common cause of death was TC-specific mortality, suggesting the importance of thyroid cancer treatment. The overall and cause-specific mortality risks, particularly CVD mortality risk, did not differ between TC patients and the general population.